الضغوط والحاجات النفسية والاجتماعية لدى عينة من آباء وأمهات الأطفال المعاقين ذهنيا: دراسة فارقة عبر حضارية - الوكيل، سيد أحمد محمد (جامعة الإمام محمد بن سعود الاسلامية - عمادة البحث العلمي, 2015)
استهدفت هذه الدراسة التعرف على طبيعة الضغوط والحاجات النفسية والاجتماعية التي يُعاني منها آباء وأمهات الأطفال المُعاقين ذهنياً في كل من مصر والسعودية، والفروق عبر الحضارية في هذه الضغوط والحاجات، وتكونت العينة من: العينة المصرية: وتكونت من 200 من آباء وأمهات الأطفال المُعاقين ذهنياً. العينة السعودية: وتكونت من ٢٠٠ من آباء وأمهات الأطفال المُعاقين ذهنياً. وقد أكدت النتائج على أنه: 1- وجد فروق دالة إحصائياً بين آباء وأمهات العينة المصرية في الضغوط النفسية. 2- توجد فروق دالة إحصائياً بين آباء وأمهات العينة السعودية في الضغوط النفسية. 3- توجد فروق دالة إحصائياً بين آباء وأمهات العينة المصرية في الحاجات النفسية والاجتماعية. 4- توجد فروق دالة إحصائياً بين آباء وأمهات العينة السعودية في الحاجات النفسية والاجتماعية. 5- توجد فروق دالة إحصائياً في الضغوط النفسية الواقعة على آباء المُعاقين ذهنياً في كلٍ من مصر والمملكة العربية السعودية. 6- توجد فروق دالة إحصائياً في الضغوط النفسية الواقعة على أمهات المُعاقين ذهنياً كل من مصر والمملكة العربية السعودية. 7- توجد فروق دالة إحصائياً في الحاجات النفسية والاجتماعية التي يُعاني منها آباء المُعاقين ذهنياً في كل من مصر والمملكة العربية السعودية. 8- توجد فروق دالة إحصائياً في الحاجات النفسية والاجتماعية التي يُعاني منها أمهات المُعاقين ذهنياً في كل من مصر والمملكة العربية السعودية.
This study aims to know the nature of social and psychological stresses and needs of fathers and mothers of mental disabled children in Egypt and Saudi Arabia, as well as the cross-cultural differences among these stresses and needs. The study sample consisted of two samples: the Egyptian sample which consists of (200) fathers and mothers of mental disabled children in Egypt, and the Saudi sample which consists of (200) fathers and mothers of mental disabled children in Saudi Arabia. The results shows the following: 1- There are statistically significant differences between Egyptian fathers and mothers in psychological stresses. 2- There are statistically significant differences between Saudi fathers and mothers in psychological stresses. 3- There are statistically significant differences between Egyptian fathers and mothers in social and psychological needs. 4- There are statistically significant differences between Saudi fathers and mothers in social and psychological needs. 5- There are statistically significant differences in psychological stresses between Egyptian and Saudi fathers of mental disabled children. 6- There are statistically significant differences in psychological stresses between Egyptian and Saudi mothers of mental disabled children. 7- There are statistically significant differences in psychological and social needs between Egyptian and Saudi fathers of mental disabled children. 8- There are statistically significant differences in psychological and social needs between Egyptian and Saudi mothers of mental disabled children.
Keywords: الأطفال المعوقون ذهنيا -- الآباء و الأمهات -- الضغوط النفسية -- الضغوط الاجتماعية -- مصر -- السعودية